BENTUK PENYAJIAN TARI BAROMBAI DALAM UPACARA TURUN KA SAWAH DI NAGARI PADANG LAWEH KECAMATAN KOTO VII KABUPATEN SIJUNJUNG - Rahmadhani Amelia; Fuji Astuti; Darmawati Darmawati (FBS Universitas Negeri Padang, 2018)
Abstract This study was aimed to describe performance of Barombai dance on Turun ka sawah ceremony in Nagari Padang Laweh Kecamatan Koto VII Kabupaten Sijunjung. Type of this study was qualitative with analytic descriptive mthod. The study object was performance of Barombai dance on Turun ka sawah ceremony in Nagari Padang Laweh Kecamatan Koto VII Kabupaten Sijunjung with data were both primary and secondary. Instrument used in this study was the researcher. Technique of data collection were done by using library research, observation, interview and documentation. Furthermore, data were analyized accurately and selected as needed and it’s relation with the posed problem. Result of this study showed that performance of Barombai dance was combination of imitation motion activities at farmland namely mancangku (mencangkul), mambuek luluak (membuat lumpur), mancampak (membuang), manyimbua (menyiram), malunyah (menginjak), manjapuik baniah (menjemput benih), batanam/ ma atu (menanam), basiang (menyiang) dan mananti padi tobiek (menunggu padi masak). Iringan musik tari Barombai dari talempong pacik dan gendang serta dendang yang khas “dadoi”. Performance of this dance was performed at farmland by using floor pattern of linear progression that were using horizontal and circle. Costume which was used namely baju kurung, kain sarung and takuluak which used on a head. Music of this dance used talempong pacik, gendang and unique dendang “dadoi” Keywords: Performance, Barombai Dance, Turun ka Sawah Ceremony